2013
DOI: 10.1002/oby.20586
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between weight status and doctor shopping behavior-evidence from Australia

Abstract: Objective: A recent study has suggested that overweight and obese people are more likely to consult a range of physicians (doctor shopping). The consistency of this finding with multiple measures of doctor shopping and controls for socioeconomic circumstances was interrogated. Design and Methods: Ninety-nine thousand four hundred seven Australians aged 45 and over who had sought primary healthcare at least five times within 6 months of a survey (2006)(2007)(2008). (i) The count of different physicians consulte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…This is supported by findings from a recent study in the same geographic area which documented a higher risk of avoidable hospital admissions among people who reported multiple unhealthy lifestyles [23]. For a fuller overview of engagement with the health system, it would be useful for future studies to investigate patterns of overall health service use across primary, secondary and tertiary healthcare [24]. …”
Section: Discussionmentioning
confidence: 68%
“…This is supported by findings from a recent study in the same geographic area which documented a higher risk of avoidable hospital admissions among people who reported multiple unhealthy lifestyles [23]. For a fuller overview of engagement with the health system, it would be useful for future studies to investigate patterns of overall health service use across primary, secondary and tertiary healthcare [24]. …”
Section: Discussionmentioning
confidence: 68%
“…In contrast, an analysis of Australian patients did not find a difference in doctor shopping by weight status (17). A few factors may contribute to their null findings.…”
Section: Discussionmentioning
confidence: 75%
“…Narcotics, orthopaedic trauma Okumura 2016 [48] Insurance database Benzodiazepines Pradel 2004 [45] Prescription database Buprenorphine Agrawal 2016 [7] Visiting ≥1-5 doctors during the same illness episode. Questionnaire Diabetes Chang 2012 [28] Insurance database Colorectal cancer Feng 2013 [35] Questionnaire Overweight Gudzune 2014 [13] Internet-based survey Overweight Gudzune 2013 [37] Claims data, health risk assessments Overweight Kappa 2016 [9] Retrospective study, medical records Nephrolithiasis, opioids…”
Section: Discussionmentioning
confidence: 99%
“…In studies enrolling patients with chronic conditions such as diabetes [7], eye floaters [26], or nephrolithiasis [9], the definition of doctor-shopping specified a higher number of visits, whereas in cases of urgent conditions or infections, definitions specified a timeframe and were, for example, limited to one day [27] or to the same illness episode [6,10,12,[28][29][30][31][32][33][34]. Studies focusing on the evaluation of doctor-shopping in general medicine or primary doctor facilities had longer timeframes of 1 year [35,36], 2 years [37], or even 3 years [38]. Definitions of doctorshopping in the studies identified are presented in Table 3.…”
Section: Definition Of Doctor-shoppingmentioning
confidence: 99%
See 1 more Smart Citation